0402 Efficacy of FT218, a Once-Nightly Sodium Oxybate Formulation, in Patients With Narcolepsy: Post-hoc Sensitivity Analyses From the REST-ON Trial. (25th May 2022) - Kushida, Clete; Roth, Thomas; Thorpy, Michael; Seiden, David; Dubow, Jordan; Gudeman, Jennifer
Abstract: Introduction: In REST-ON, once-nightly sodium oxybate (ON-SXB; FT218) achieved significant improvement (P<0.001) vs placebo for all coprimary endpoints: Maintenance of Wakefulness test (MWT) mean sleep latency, Clinical Global Impression of Improvement (CGI-I) rating, and weekly number of cataplexy attacks (NCA). Methods: Individuals aged ≥16 years were randomized 1:1 to receive ON-SXB (1 week, 4.5 g; 2 weeks, 6 g; 5 weeks, 7.5 g; 5 weeks, 9 g) or placebo. Post-hoc sensitivity analyses were conducted with methods to handle missing data: completer population; placebo-based multiple imputation (MI) with missing not at random assumption; analysis of covariance (ANCOVA); and tipping point-based MI of worsening values until P>0.05. Results: Completers (ON-SXB, n=69; placebo, n=79) showed significant improvement (P<0.001) with 6, 7.5, and 9 g ON-SXB vs placebo on all coprimary endpoints; with 9-g dose, mean (95% CI) differences vs placebo were 6.0 min (3.3–8.7) on MWT and –6.6 (–9.6 to –3.6) in NCA; 72.3% and 31.6%, respectively (odds ratio [OR], 5.7 [95% CI: 2.8–11.6]), were CGI-I responders. All ON-SXB doses achieved significant improvement (P<0.001) vs placebo on all coprimary endpoints with placebo-based MI and ANCOVA. With placebo-based MI, mean (95% CI) differences vs placebo (9-g dose) were 5.4 min (2.8–8.0) on MWT and –6.4 (–11.3 to –3.7) in NCA; 63.0% and 28.5%, respectively (OR, 4.3 [95% CI: 2.3–8.0]), were CGI-I responders. With ANCOVA, mean (95% CI) differences vs placebo (9-g dose) were 6.0 min (3.6–8.5) on MWT and –6.4 (–9.0 to –3.8) in NCA; CGI-I rating difference was –1.0 (–1.3 to –0.7). With MWT tipping point MI, between-treatment differences lost significance with worsening of 7.0, 5.2, and 4.3 min from baseline for 6, 7.5, and 9 g, respectively (implausible for 7.5- and 9-g doses). When withdrawals from ON-SXB were imputed as "not improved, " CGI-I remained significant (all 3 doses, P<0.001). Mean NCA remained significant for all 3 doses vs placebo with worsening trajectories imputed; positive results were not tipped over with plausible values. Conclusion: These results support the robustness of the primary efficacy data for ON-SXB for narcolepsy treatment. Support (If Any): Avadel Pharmaceuticals